Analysis of the work environment of the employees of the authority of Petra Tourism Development Authority - Al-Saeedat, Hassan Salman Musa (Journal of Economic, Administrative and Legal Sciences, 2018)
This study aims to know about the Petra region authority employee's satisfaction toward the work environment with its two sides the administrative and financial side. A group of worker has been chosen consisted of 140 male and female employees to as a sample for this study with age (25-50) years old. Descriptive and analytical criteria have been used with a questioner list that was included (18) question the first sixth questions focused on the financial measures while the other twelfth questions focused on the administrative measures and reinforcement. The study showed that (64.2%) of group of workers were satisfied about the work environment, (59%) of workers were financially satisfied and (66.8%) of works were satisfied with administrative. Consequently, the study had some recommendations which presented by employees themselves as the following:1- Takins care about the physical environment such as providing a proper heating system, safety methods, yards and providing modern furniture.2- Taking more care about phycology reinforcement, running some debates and form particular groups for work.3- Increasing the level of the reinforcement way which has been followed.4- Reinforcing and sponsor the creative employees.5- Providing a reward at the end of each month.6- Providing a luxury such as determining a reward at the end of employee service, creating a saving found and creating an organization for such employee facilities and activities.
Keywords: work environment; employee satisfaction; job well-being; Petra region